PENGARUH KOMPENSASI NON FINANSIAL, MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN - Linda, Agata; Windayanti, Windayanti (Economic Faculty, Attahiriyah Islamic University, 2018)
The purpose of this research is to explain the influence of nonfinancial compensation, motivation and job satisfaction on employee performance of PT Bakrie Pipe Industries Bekasi partially and simultaneously. The research this use quantitative approach by using interview and questionnaire. The samples using purposive sampling technique with Slovin formula resulted 217 respondent samples. Data analysis used validity test, reliability test, multiple linear regression test. The result of the research found that: (1) Nonfinancial compensation has no significant effect on employee performance; (2) Motivation have significant effect on employee performance; (3) Job satisfaction have significant effect on employee performance; and (4) Nonfinancial compensation, motivation, and job satisfaction have significant effect on employee performance. Keywords: Nonfinancial Compensation, Motivation, Job Satisfaction, Employee Performance